Fostering Digital Citizenship for Safer Digital School Environments: A Systematic Analysis of Cyberbullying Prevention Strategies Among Students - WINARNO; DESTINY; SALSABILA WAHYU MAULUDINA; ICA KLARA MONICA (Universitas PGRI Kanjuruhan Malang, 2026)
The era of Society 5.0 and the digital transformation of education present serious challenges, including the rise of cyberbullying among students. Although previous research has primarily focused on curriculum guidelines and technical constraints as separate issues, little attention has been paid to developing a comprehensive prevention framework that integrates individual attitudes within a cohesive macro-level ecosystem. This study aims to analyze cyberbullying prevention strategies through a digital citizenship approach to create a safe digital school environment. The method used is a Systematic Literature Review (SLR) of 25 high-quality studies. The conceptual novelty of this study lies in integrating global digital citizenship with national civic values and theories of moral development. The thematic synthesis results revealed a prevention ecosystem based on three pillars: integrating digital ethics into Pancasila education, providing a 24/7 anonymous reporting system, and enhancing communication between schools and parents. Sustainable digital safety relies on integrating three key pillars that encourage shared responsibility and help create a safer school environment.